Rotenone impairs oxidant/antioxidant balance both in brain and intestines in zebrafish - ALTURFAN, EBRU IŞIK (TAYLOR & FRANCIS LTD, 2019)
Aim of the study: Rotenone is a commonly used pesticide that inhibits complex I of the mitochondrial electron transport system. Rotenone exposed rats demonstrate many characteristics of Parkinson Disease (PD). Oxidative stress is one of the hallmarks of PD, being the major sources of ROS in the DA neurons. In recent years the strong connection between the intestinal environment and the function of the central nervous system (CNS) has gained widespread popularity. In order to explain the mechanism underlying the GI dysfunction in PD, we aimed to investigate oxidant-antioxidant status in the brain and intestine, as well as locomotor activity, in rotenone exposed zebrafish. Materials and methods: Adult zebrafish were exposed to 2 mg/L rotenone for 30 days. At the end of the experiment, locomotor activity was determined by simple observation. Lipid peroxidation (LPO), nitric oxide (NO) levels, superoxide dismutase (SOD), catalase (CAT) and glutathione-S-transferase (GST) activities were determined in the homogenates. Results: Locomotor activity decreased in the rotenone exposed zebrafish. LPO increased in both brain and intestines whereas NO increased only in the brain. Decreased GST and CAT activities were found in both tissues whereas SOD activity decreased only in the intestines. Conclusion: As a conclusion, the results of our study support the connection between gut and brain axis in rotenone exposed zebrafish by means of oxidative stress and NO for the first time in literature.
Keywords: Rotenone; brain; intestine; oxidant; antioxidant; nitric oxide; PARKINSONS-DISEASE; MODEL; ENVIRONMENT